A roadmap to identifying and filling shortfalls in Neotropical ornithology. (21st August 2020) - Lees, Alexander Charles; Rosenberg, Kenneth V; Ruiz-Gutierrez, Viviana; Marsden, Stuart; Schulenberg, Thomas S; Rodewald, Amanda D
Abstract: Securing the long-term resilience of the world's most speciose avifauna, that of the Neotropics, requires spatially and temporally explicit data to inform decisions. We examine gaps in our knowledge of the region's avifauna through the lens of the biodiversity shortfall concept: the gaps between realized knowledge and complete knowledge. This framework serves as a useful tool to take stock of the last 25 yr of Neotropical ornithological work since the untimely death of Ted Parker. Here, we highlight 7 key shortfalls: taxonomy, distribution, abundance, evolutionary patterns, abiotic tolerances, species traits, and biotic interactions. We then propose an eighth—and new—"Parkerian" shortfall that reflects a lack of basic natural history knowledge key to understanding how species might respond to environmental challenges. Bridging this shortfall will help reverse declines by informing reintroduction, recovery network, and habitat restoration efforts. We discuss the challenges imposed by each shortfall and how strategies such as citizen-science initiatives and technological advances can either remedy or mitigate the uncertainty they generate.